Improving Interagency Information Sharing Using Technology Demonstrations The Legal Basis for Using New Sensor Technologies for Counterdrug Operations Along the U.S. Border - Gonzales, Daniel (RAND Corporation, 2014)
The Department of Defense (DoD) has developed new sensor technologies to support U.S. forces in Iraq and Afghanistan; these technologies are potentially useful for counterdrug operations along the southern U.S. border, but there are legal questions regarding how they may be used and how sensor information may be shared between federal agencies in domestic operations. This report examines federal law and DoD policy to answer these questions.